2019
DOI: 10.1111/vco.12531
|View full text |Cite
|
Sign up to set email alerts
|

The effects of local irradiation on circulating lymphocytes in dogs receiving fractionated radiotherapy

Abstract: Localized radiation therapy can be an effective treatment for cancer but is associated with localized and systemic side effects. Several studies have noted changes in complete blood count (CBC) parameters including decreases in the absolute lymphocyte count (ALC) and increases in the neutrophil:lymphocyte ratio (NLR). These changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…We showed significant differences in absolute lymphocyte count and neutrophillymphocyte ratio within 90 days of treatment with worsened lymphopenia grade in 66.7% of these patients. This is consistent with the literature (45,79). Unfortunately, the sample size of available patients was too small for further analysis of the effect of post-SBRT lymphopenia on survival outcome and what demographic or tumor factors may influence these changes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We showed significant differences in absolute lymphocyte count and neutrophillymphocyte ratio within 90 days of treatment with worsened lymphopenia grade in 66.7% of these patients. This is consistent with the literature (45,79). Unfortunately, the sample size of available patients was too small for further analysis of the effect of post-SBRT lymphopenia on survival outcome and what demographic or tumor factors may influence these changes.…”
Section: Discussionsupporting
confidence: 89%
“…Adoptive cellular therapy using activated canine natural killer cells has been investigated in an osteosarcoma model (42), while modulation of the canine tumor microenvironment through radiation and immunotherapy has been investigated using indoleamine deoxygenase inhibition (43) as well as nanotechnology-based immune adjuvants (44). Additionally, dogs receiving fractionated radiotherapy developed significant and sustained lymphopenia after treatment (45), which has been similarly shown in human radiation therapy to effect clinical outcomes in oropharyngeal tumors (46). Moving forward, investigations into the combined use of SBRT with immunotherapy in canine cancer patients may serve as a translational model due to the similar immunomodulatory effects as human cancers (47).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the targeted nature of IM/IGRT, it was expected that concurrent use of chemoradiation for CGUC would be well tolerated. However, given that dogs undergoing definitive intent RT are known to experience clinically relevant decreases in total white blood cell count, it is not surprising that severe cytopenias might result from the combination of relatively high dose RT with cytotoxic chemotherapy 20,21 . Indeed, in our study, 56% of dogs that received concurrent MTX and RT developed hematopoietic adverse events, and 64% were classified as grade 3 or 4 complications.…”
Section: Discussionmentioning
confidence: 65%
“…[ 18 ] RT caused significant lymphopenia compared with baseline. [ 19 ] Lymphopenia may be associated with poor outcomes in cancer patients treated with RT. [ 20 ] A study showed that pretreatment lymphopenia is an independent prognostic factor for patients with EC.…”
Section: Discussionmentioning
confidence: 99%